Phylogeographic analysis reveals strong geographical structuring in the klipspringer, Oreotragus oreotragus - Le Roex, Nikki (Department of Molecular and Cell Biology, 2016)
The klipspringer, Oreotragus oreotragus, occurs from the Western Cape of South Africa through to north-east Africa. Anthropological factors such as hunting have eradicated the klipspringer in parts of its former range and efforts have begun to reintroduce klipspringer back into these areas. This has highlighted the need for the proper understanding of the genetic variation, phylogeographic and population structure of the species, as well as the genetic validity of the 11 subspecies designations. Mitochondrial control region and cytochrome b sequence data were used to investigate these topics using blood, faecal and museum specimens. Cytochrome b and control region fragments were amplified in 83 and 60 samples respectively, out of a total sample set of 89 individuals. The generation of authentic mitochondrial DNA control region fragments proved difficult, with both Numt and PCR recombinant sequences identified after amplification. High levels of genetic variation were observed in the klipspringer, with cytochrome b and control region haplotype diversities of 0.78 and 0.98 respectively. Phylogenetic and network analyses showed the distinct geographical clustering of individuals into two major groups, south/south-western (S/SW) and east/north-eastern (E/NE), with the S/SW further split into two divergent groups. This suggests that the two S/SW groups were separated and isolated as a result of shifting climatic conditions in the late Pl iocene/early Pleistocene, after which secondary contact occurred and klipspringer moved upwards from southern Africa to colonise the east. The results from this study have conservation implications with respect to translocation policies, suggesting that translocations should only occur within the geographic groups identified in order to avoid outbreeding depression.